Students’ understanding of non-inertial frames of reference - S. Küchemann (American Physical Society, 2020)
The concepts of the Coriolis and the centrifugal force are essential in various scientific fields and they are standard components of introductory physics lectures. In this paper, we explore how students understand and apply concepts of rotating frames of reference in the context of an example lecture demonstration experiment. We found in a predict-observe-explain setting that after predicting the outcome prior to the demonstration, only one out of five physics students correctly reported the observation of the trajectory of a sphere rolling over a rotating disc. Despite this low score, a detailed analysis of distractors revealed a significant improvement in the distractor choices during the observation of the experiment. In this context, we identified three main preconceptions and learning difficulties: The centrifugal force seems to be only required to describe the trajectory if the object is coupled to the rotating system, the inertial forces cause a reaction of an object on which they act, and students systematically mix up the trajectories in the stationary and the rotating frame of reference. Furthermore, we captured students’ eye movements during the predict task and found that physics students with low confidence ratings focused longer on relevant task areas than confident students despite having a comparable score. Consequently, this metric is a helpful tool for the identification of preconceptions using eye tracking. Overall, the results help us to understand the complexity of concept learning from demonstration experiments and provide important implications for instructional design of introductions to rotating frames of reference.